2018
DOI: 10.5958/2249-880x.2018.00001.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foliar application of boron and zinc on growth and flowering characters in African marigold cv. Pusa Narangi Gainda

Abstract: Effect of rooting hormone and media on root induction in poinsettia 7 (Euphorbia pulcherrima Willd.) Effect of foliar application of boron and zinc on growth and flowering characters in African marigold

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(43 reference statements)
2
1
0
Order By: Relevance
“…This might be due to sufficient nutrients available for widely spaced plants to produce vigorous plant growth with maximum number of stems. A similar result was reported by Singh and Kumar (2009).…”
Section: Number Of Stems Per Plantsupporting
confidence: 91%
See 1 more Smart Citation
“…This might be due to sufficient nutrients available for widely spaced plants to produce vigorous plant growth with maximum number of stems. A similar result was reported by Singh and Kumar (2009).…”
Section: Number Of Stems Per Plantsupporting
confidence: 91%
“…This might be due to availability of more area per plant for absorption of nutrients and moisture, no shading effect which ultimately increased the rate of net photosynthesis and translocation of assimilates to the storage organs, which promotes more flowers in plant compared to less space per plant. A similar result was found in Singh and Kumar (2009).…”
Section: Number Of Flowers Per Plantsupporting
confidence: 89%
“…The weather conditions in most parts of our country are relatively favourable for stevia farming. It is mainly grown in northern part of the country like states of Himachal Pradesh, Punjab, Uttar Pradesh, Rajasthan, Madhya Pradesh, Chhattisgarh and in some parts of Karnataka [3]. However, the cultivation of this remarkable herb is not without challenges.…”
Section: Introductionmentioning
confidence: 99%
“…However, in many studies, the foliar application of Zn has shown 6 to 20 times more beneficial than the basal application, and foliar Zn has proved to be an efficient and economic method to significantly increase crop growth and yield. Foliar ZnSO 4 improved length and width of leaf, weight and diameter of corm in gladiolus (Hembrom et al, 2015), length of rachis and duration of flowering in gladiolus (Singh et al, 2015), plant and flower attributes in marigold (Shah et al, 2016), bud initiation, bud diameter and flower weight in African marigold (Singh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%